If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6*7+y/2=43
We simplify the equation to the form, which is simple to understand
6*7+y/2=43
Simplifying:
+42+y/2=43
Simplifying:
+42 + 0.5y=43
We move all terms containing y to the left and all other terms to the right.
+ 0.5y=+43-42
We simplify left and right side of the equation.
+ 0.5y=+1
We divide both sides of the equation by 0.5 to get y.
y=2
| 7*2.5=x | | 7(x+2)+31=-2x | | x-.2x=10000 | | 22+3x=43 | | 3x+2=5+2 | | 14x+14=6x+238 | | 7*2.5+n=17.5 | | 14-9x=82-23x | | 5*2=4(x-8) | | 10h-3h=3h+18 | | 6ln-4k=4lm-4 | | 1=2y-4 | | m/5+1.5=2 | | -1-1-1-1= | | 8z=4z | | 5(2x+3)=4(2x+1)+15 | | d=3*55+35 | | 2mp-31=4 | | 82.5=1.5s | | N/3-7=17 | | (5p-3)+(2p-3p)= | | x^2-12+52=0 | | 4*3+2b=22 | | 25=11a-8 | | x^2+12+52=0 | | 75-s=35 | | 2.8=0.7y | | 8x+2=10+(6x-2) | | 5/3x+7/4=(-2)/8x | | 5x+2x-3=-3x+9x | | 16x^2+0-25=0 | | 4/3(2s+9/4)-2=9 |